Analisis Rata-Rata Asupan Kalsium dan Zat-Besi Remaja Berdasarkan Status-Ekonomid di Pulau Jawa - Mulyani, Erry Yudhya (Jurnal Nutrire Diaita (Ilmu Gizi), 2015)
AbstractAccording to RISKESDAS-2010 the prevalence of skinny-nutritional status (BMI/A) was 9.5% for men whereas women 4.4%. In human’s research study, the absorption of hem and non-hem iron in inhibition by calcium supplements and milk products. The aim of this study was to analyze the average intake of calcium-iron in adolescence based-on socio-economic status in Java-Island. This study was cross-sectional design, using RISKESDAS-2010 data analyzed by T-test-Independent and Regression. Most of respondents were male as 51.2%, 28.3% from East-Java, in quintile 5 36.4%, and 73.9% were living in-urban areas. There was difference Fe-intake by-sex (t=-3184;p<0.05), but no-difference was found Ca-intake by-sex (t=-0282;p≥0.05). There were differences of Ca-Fe intake based-on age (tCa=2,089;p<0.05;tFe=-2525;p<0.05). However, no-differences Fe-intake for adolescent-males based-on age (t=-0761;p≥0.05). There were differences of Ca-Fe intake based-on areas and socio-economic status (tCa=3,182;TFe=-4981;p<0.05) and (tCa=-2652;TFe=2.191;p<0.05). There was significant difference of Fe-intake by-sex (t=-3184;p<0.05), but not the Ca-intake (t=-0282;p≥0.05). There were differences of Ca-Fe intake based-on age (tCa=2,089;p<0.05;tFe=-2525;p<0.05). However, no-difference was observed for Fe-intake for adolescent males based-on age (t=-0761;p≥0.05). There were differences of Ca-Fe intake based-on areas and socio-economic status (tCa=3,182;TFe=-4981;p<0.05) and (tCa=-2652;TFe=2.191;p<0.05). Regression analysis showed that among-girls aged 10-18 years, living in-rural and having lower-middle economy has higher-risk to decrease Ca-intake in the body up-to 63.809. The study found that there is difference intake of Ca and Fe based on the type of area and socio-economic. Balanced-nutrition education is required as an effort in the process of optimal interaction for nutrition-metabolism.  Keywords: Calcium-Iron Intake, Adolescence, Socio-economic status AbstrakMenurut RISKESDAS 2010 prevalensi status gizi (IMT/U) kurus pada laki-laki 9,5% lebih tinggi dari perempuan 4,4%. Penelitian ini bertujuan menganalisis rata-rata asupan kalsium dan zat besi remaja berdasarkan status-ekonomi di Pulau Jawa. Metode penelitian ini cross-secional design. Analisis data RISKESDAS 2010 menggunakan uji T-test Independent dan Uji Regresi. Sebagian besar responden berjenis kelamin laki-laki 51.2%, berasal dari Propinsi Jawa Timur 28.3%, berada pada quintil 5 (36.4%) dan tinggal di perkotaan 73.9%. Ada perbedaan Asupan Fe berdasarkan Jenis Kelamin (t=-3.184, p<0.05), namun tidak ditemukan perbedaan Asupan Ca berdasarkan Jenis Kelamin (t=-0.282, p≥0.05). Ada perbedaan Asupan Ca dan Fe berdasarkan umur (t=2.089, p<0.05 dan t=-2.525, p<0.05). Namun tidak ditemukan perbedaan Asupan Fe berdasarkan umur pada remaja laki-laki (t=-0.761, p≥0.05). Ada perbedaan Asupan Ca dan Fe berdasarkan tipe daerah dan social-ekonomi (tCa=3.182; tFe=-4.981, p<0.05) dan (tCa=-2.652; tFe=2.191, p<0.05). Uji regresi menunjukkan pada remaja perempuan umur 10-18 tahun, tinggal di perdesaan dan perekonomian menengah ke bawah memiliki resiko tinggi dalam menurunkan jumlah asupan Kalsium tubuh sebesar 63.809. Diperlukannya pendidikan gizi seimbang sebagai upaya dalam proses interaksi metabolisme zat gizi yang optimal. Kata kunci: Asupan Kalsium-Zat Besi, Remaja, Sosial Ekonomi